(untitled) (Applied Biological Research, 2020)
The present investigation was carried out to assess the genetic variability parameters, correlation and path analysis in 95 elite rice germplasm collections for 12 yield and its contributing traits during kharif, 2018 in a randomized block design, replicated twice. Theanalysis of variance for mean sum of squares due to genotypes showed significant differences for all the quantitative characters studied at 1 and 5% level of significance. PCV and GCV were high for traits like days to 50% flowering, tillers plant1, productive tillers plant-1, length/breadth ratio and grain yield plant-1. High heritability (> 60%) coupled with high genetic advance as percentage of mean (> 30%) was recorded for days to 50% flowering, leaf length, tillers plant-1, productive tillers plant-1, L/B ratio, grain width, 100 grain weight and grain yield plant-1indicating thepreponderance of additive gene action. The grain yield plant-1 had highly significant and positive correlation both at genotypic and phenotypic levels with tillers hill-1, productive tillers plant-1, panicle length and days to 50% flowering. High direct effects of these characters appeared to be the main reason for their strong association with grain yield except for number of productive tillers plant-1 which had strong association with yield through indirect effect (i.e. through tillers plant-1. Hence, direct selection for these characters would be very effective for further improvement of grain yield in rice and for the selection of elite genotypes.